OCCASIONAL ADNOMINAL IDIOM MODIFICATION - A COGNITIVE LINGUISTIC APPROACH - Langlotz, Andreas (International Journal of English Studies, 2009)
occasional Adnominal Idiom Modification - A Cognitive Linguistic Approach From a cognitive-linguistic perspective, this paper explores alternative types of adnoniinal modification in occasional variants of English verbal idioms. Being discussed against data extracted from the British National Corpiis (BNC), the model claims that in idioni-production idiomatic constructions are activated as complex linguistic schemas to code a context-specific target-conceptualisation. Adnominal pre- and postmodifications are one specific form of creative alteration to adapt the idiom for this purpose. Semantically, idiom-interna1 NPextension is not a uniforni process. It is necessary to distinguish two systematic types of adnominal modification: external and internal modification (Ernst 1981). While external NPmodification has adverbial function, ¡.e. it modifies the idiom as a unit, internal modification directly applies to the head-noun and thus depends on the degree of motivation and analysability of a given idiom. Following the cognitive-linguistic framework, these dimensions of idiom-transparency result from the language user's ability to remotivate the bipartite semantic structure by conceptual metaphors and metonymies.